Keanekaragaman Jenis Satwa Burung di Areal Mangrove Desa Passo Kecamatan Teluk Ambon Baguala Kota Ambon - Puttileihalat, Maya M.S.; Tuhumury, A.; Hitipeuw, J.Ch. (Universitas Pattimura, 2020)
Mangrove forests have many functions, one of which is a habitat for various water birds and birds. Birds make mangroves a habitat to find food, breed, or just rest. Birds that can be found in mangrove forests can be birds that live and nest in mangrove forests and birds that come from other habitats that only occasionally visit mangroves to find food or rest. The research method used is the Point Count method, where the observation technique is carried out at a point, and the observations are carried out over a certain period. The number of bird species recorded in the mangrove area of ​​Passo Village was 11 species from 9 genera, seven families, and seven orders. The average number of individuals recorded during the research activity was 197 individuals. 72.73% of the composition of bird species in the mangrove area of ​​Passo Village are waterbird species, including four orders from a total of 7 charges, and four families from a total of 7 families, and six genera from a total of 9 genera; while the other 27.27% are terrestrial bird species.